Children: an inheritance from the Lord. Infanticide and the value of life - Hain, RDW (2021)
Arguing from preference utilitarianism, contemporary moral philosopher Peter Singer considers infanticide permissible because infants lack the cognitive capacity to prefer life over death. Christian theologians object that Singer’s general theory offers too thin a conception of ‘the good’, fails to recognise the dependence of value on purpose and abstracts moral value from common humanity. Few confront him directly on infanticide.